2000
DOI: 10.1103/physrevlett.85.4884
|View full text |Cite
|
Sign up to set email alerts
|

Ripple Formation through an Interface Instability from Moving Growth and Erosion Sources

Abstract: The propagation of material interfaces is investigated under the action of a localized moving source which deposits or removes material. Among others the latter process applies to beam cutting techniques. We develop a Kuramoto-Sivashinsky-type model and find a new type of ripple forming mechanism. This theory offers a new explanation for the occurrence of striation patterns which often degrade the quality of cutting edges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 22 publications
2
20
0
Order By: Relevance
“…13 They assumed that the surface profile evolves according to a generalized Kuramoto-Sivashinsky equation, which takes into account the inhomogeneity of the disturbance. The competition between a negative surface tension , which tends to increase the area of the surface, and a positive coefficient , which accounts for the surface diffusion, leads to a periodic structuring of the surface with wavelength ϳͱ/.…”
Section: Discussionmentioning
confidence: 99%
“…13 They assumed that the surface profile evolves according to a generalized Kuramoto-Sivashinsky equation, which takes into account the inhomogeneity of the disturbance. The competition between a negative surface tension , which tends to increase the area of the surface, and a positive coefficient , which accounts for the surface diffusion, leads to a periodic structuring of the surface with wavelength ϳͱ/.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the investigation of pattern formation processes occurring in semiconductor gasdischarge devices used for the conversion of infrared images into the visible has led to the improvement of the technical characteristics of the device [19]. Another example is the successful suppression of undesired patterns occurring by abrasive waterjet cutting [20]. Finally, we want to mention works on control of the traffic flow.…”
Section: Introductionmentioning
confidence: 98%
“…Microscopic analysis showed that the eroded surface of target materials 1Cr9Mo1VNbN, 1Cr11MoCo3W2, and 1Cr11MoV had some regular erosion ripples as previously seen in the literature, 14,18,19,21,22 while the eroded surface of target materials 2Cr11MoVNbN and 2Cr12NiMo1W1V had only random concaveconvex scars, which is shown in Figure 4. Apparently, not all plastic materials can produce erosion ripples.…”
Section: Single-angle Erosion and Ripple Formationmentioning
confidence: 66%